Studying the mechanical and electrical properties of epoxy with PVC and calcium carbonate filler - Abd, Abeer (International Journal of Engineering and Technology, 2014)
In the present research composite material was prepared from epoxy and PVC reinforced with calcium carbonate as a filler material with different percent weight ratios (0.6,1.2,1.8 and 2.4) g.The effect of different weight ratios of calcium carbonate particles and PVC different content on electrical permittivity , dielectrical loss constant, hardness ,young modulus and compression strength were studied. Electrical properties of these composites were investigated by using Fourier transform infrared spectroscopy (FTIR) to study the bonds which enhanced the insulating properties of epoxy material compounded with filler and PVC. The inclusion of CaCO3  in epoxy and (PVC) polymer matrices greatly enhances the physical and mechanical properties of the composite.The experimental results also show that sample (5) compounded with 2.4 g of Calcium Carbonate has the minimum dielectric loss therefore it had the best insulating properties.  The compression strength, young modulus, hardness decrease with filler content increase and PVC compound decreased. The maximum electrical permittivity in sample (3) compounded with 1.2 g of calcium carbonate and 4.8 g of PVC. Cost also can be reduced by the addition of filler material. .
Keywords: PVC; Epoxy; Filler; Calcium Carbonate; FTIR; Dielectric Properties.